KONSERVASI PENYU DI PANTAI PALOH KABUPATEN SAMBAS - Putri, Nabila Aulia; Pebriano, Valentinus; Purnomo, Yudi (JMARS: Jurnal Mosaik Arsitektur, 2024)
Indonesia is home to six of the world's seven species of sea turtles. Since 1981 internationally sea turtles have been included in the red list of the International Union for Conservation of Nature Resources (IUCN) and Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). In 1990, turtles were protected by Law Number 5 of 1990 concerning the Conservation of Biological Natural Resources and their Ecosystems. Its existence is protected because sea turtles act as a balancer of marine ecosystems. Sea turtles are endangered due to high exploitation, damaged habitats and the threat of predators. One of the turtle nesting and conservation areas in Indonesia is in Paloh Beach, Sambas Regency, West Kalimantan Province starting from 2009-present. Design of the Sea Turtle Conservation Center in Paloh Beach, Sambas Regency as infrastructure to support turtle monitoring activities, research and education centers, information centersand tourism. The design location is at Tanjung Api Beach, Sebubus Village, Paloh District, Sambas Regency, West Kalimantan. The design theme is adjusted to the principle of conservation, namely "2P" (Protection and Preservation) meaning protection of life support systems (Protection), and preservation of the use of biological natural resources and their ecosystems (Preservation). This design uses field research methods (field reserch) which includes observation, documentation and interview techniques. The design results contain several masses which include management buildings, infor masi centers, inns, monitoring posts, research buildings, turtle shelter buildings, semi-natural nests and others. The buildings above are grouped based on conservation, research, education and tourism functions. With the existence of the Sea Turtle Conservation Center in Paloh Beach, it is hoped that it can be a place for conservation and maintain the sustainability of turtle habitat.